Conformal supergravity in twistor-string theory - Berkovits, Nathan [UNESP]; Witten, Edward (Springer Nature, 2004)
Conformal supergravity arises in presently known formulations of twistor-string theory either via closed strings or via gauge-singlet open strings. We explore this sector of twistor-string theory, relating the relevant string modes to the particles and fields of conformal supergravity. We use the twistor-string theory to compute some tree level scattering amplitudes with supergravitons. Since the supergravitons interact with the same coupling constant as the Yang-Mills fields, conformal supergravity states will contribute to loop amplitudes of Yang-Mills gluons in these theories. Those loop amplitudes will therefore not coincide with the loop amplitudes of pure super Yang-Mills theory. © SISSA/ISAS 2004.
Keywords: Classical Theories of Gravity; Superstrings and Heterotic Strings; Topological Strings